Workshop Public Speaking Melatih Siswa Terampil Bicara di Depan Umum - Idawati Idawati; Benny Handayani; Khairul Anwar; Ayudia Putri; Aprillia Ratna Angela (Community Education Engagement Journal, 2019)
This community service activity aims to provide OSIS students with skills in publik speaking to train OSIS students to be skilled in publik speaking at Rumbai Sports High School in Pekanbaru. The material provided in the form of "Publik speaking Workshop Training Skilled Students Speak in Public". This material was given to students of OSIS at the Pekanbaru High School of Sports in Tegal City with a total of 35 participants consisting of OSIS students and Extracurricular Trustees. The results of this activity are (1) giving knowledge in the field of publik speaking to OSIS students so that they are skilled in publik speaking (2) students are expected to be able to apply their publik speaking knowledge to realize the vision and mission of the School.